2017
DOI: 10.1080/09603409.2017.1389100
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion fatigue testing: the combined effect of stress and high temperature corrosion

Abstract: A corrosive environment can have a detrimental effect on the fatigue life of a material due to a change in failure mechanism. Attempts have been made to replicate this change on nickel-base superalloy CMSX-4 cast in the <001> orientation. Fatigue testing in air, of this material typically produces a fracture on an angle of approximately 55° which is consistent with the fracture having propagated on a {111} slip plane. The aim of the research was to fatigue test in a corrosive environment with the purpose of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…One area where monitoring systems need to be developed further is compound degradation; this is the interactions of more than one failure mechanism to accelerate the degradation process. One example is corrosion fatigue where the presence of corrosive fluids (such as salt water) reduces the strength of materials undergoing loading (Adedipe, Brennan, and Kolios 2016;Wang et al 2016;Chapman et al 2017). Physical phenomena (such as impacts, fatigue, stress or high temperatures), chemical phenomena (such as corrosion) and biological phenomena (such as bacteria, termites or fungi) can all interact to accelerate degradation (D'Amico et al 2019).…”
Section: Monitoringmentioning
confidence: 99%
“…One area where monitoring systems need to be developed further is compound degradation; this is the interactions of more than one failure mechanism to accelerate the degradation process. One example is corrosion fatigue where the presence of corrosive fluids (such as salt water) reduces the strength of materials undergoing loading (Adedipe, Brennan, and Kolios 2016;Wang et al 2016;Chapman et al 2017). Physical phenomena (such as impacts, fatigue, stress or high temperatures), chemical phenomena (such as corrosion) and biological phenomena (such as bacteria, termites or fungi) can all interact to accelerate degradation (D'Amico et al 2019).…”
Section: Monitoringmentioning
confidence: 99%
“…It was found that the corrosion fatigue resistance tended to vary after plastic deformation of the steels in relation to their strain capacity. Chapman et al [6] studied the effect of temperature on corrosion fatigue. It was found that the corrosion fatigue crack propagation rate increased with the increase of temperature.…”
Section: Introductionmentioning
confidence: 99%